Resilience underground: understanding earthworm biomass responses to land use changes in the tropics - Md Sharif, Badrul Azhar; van der Meer, Peter; Sterenborg, Rutger F.; Yahya, Muhammad Syafiq; Razi, Norhisham; Burhanuddin, Maisarah; Rookmaker, Jasmijn; Sahimi, Nur Syarihah; van der Pal, Welmoed; Nobilly, Frisco; Mohd Azam, Siti Aisyah; Ubachs, Meriam; et al. (Elsevier, 2024)
Soil biodiversity, like terrestrial biodiversity, is currently under threat by changes in land use. Intensively managed farming activities with agrochemicals have degraded both soil biodiversity and health. However, little is known about how these changes in land use affect the distribution of earthworm biomass in Southeast Asia. We conducted earthworm sampling across multiple habitats, including lowland forests, exotic monoculture plantations (e.g., oil palm and rubber tree), and agroforestry orchards. To survey earthworm populations, we excavated the top 30 cm of soil at 18 sites encompassing 399 plots distributed across natural and human-modified ecosystems in Selangor and Negeri Sembilan, Peninsular Malaysia. We found that earthworm abundance was negatively related to increasing soil compaction, leaf litter weight, soil pH, and undergrowth height, whereas it was positively associated with increasing undergrowth and canopy cover. Our findings demonstrated that agroforestry orchards, rubber tree plantations, and mature oil palm plantations had higher earthworm abundance than those in logged lowland forests. Earthworm abundance in unlogged lowland forests and young oil palm plantations, on the other hand, was lower than in logged lowland forests. Overall earthworm weight was greater in rubber tree plantations, agroforestry orchards, mature oil palm plantations, and unlogged lowland forests than those in logged lowland forests, while young oil palm plantations exhibited lower earthworm weight than logged lowland forests. Our data indicate that increases in soil compaction and leaf litter weight were associated with decreased earthworm weight. These results demonstrate the importance of site-level habitat management for maintaining healthy earthworm populations and soil biodiversity.